Morphological and molecular evidence of Oslerus osleri (Nematoda: Filaroididae) in the Andean fox (Lycalopex culpaeus) - Gomez Puerta, Luis A. (2021)
Oslerus osleri is a cosmopolitan filaroid nematode that parasitizes the respiratory system of domestic and wild canids. Natural infection by O. osleri is reported in the Andean fox (Lycalopex culpaeus) in this study. Nematodes, enclosed in small and compact fibrous nodules of 1 to 5 mm in diameter, were found on the surface of the trachea near the bronchial bifurcation on four Andean foxes during necropsy (one from Cuzco, Peru and three from Northwestern Patagonia in Argentina). The nematodes were identified as O. osleri by morphological and molecular methods. Ribosomal and mitochondrial DNA analyses were performed amplifying the second internal transcribed spacer region (ITS-2), the partial cytochrome c oxidase 1 (cox1), and the large subunit of nuclear ribosomal RNA (LSU rRNA) genes. Sequences of the ITS-2 and LSU rRNA had a genetic variation of 1.5% and 1.0%, respectively, with previous sequences of O. osleri registered in Genbank. This is the first amplification of the cox1 gene of O. osleri and demonstrated an identity of 92% to Perostrongylus falciformis (KY365437), and 90% to Angiostrongylus cantonensis (KY779735) and Angiostrongylus costaricensis (AP017675).